The Personal Food Systems of Pre-Season NCAA Division 1 High-Contact, Low-Contact, and Non-Contact College Athletes - Jennifer Peluso (MDPI AG, 2021)
Previous research indicates that dietary habits may differ between athletes of different sports. In this cross-sectional study, we hypothesize meal frequency, food choices, and food preferences will significantly differ between contact types. The participants were athletes (n = 92; men: n = 57, body fat percent (BF%): 14.8 ± 8.4%, body mass index (BMI): 25.5 ± 5.5 kg·m−2; women: n = 36, BF%: 26.7 ± 7.3%, BMI: 22.3 ± 2.7 kg·m−2) from high-contact (HCS), low-contact (LCS), and non-contact (NCS) sports. Meal frequency, food preference, and food choice questionnaires assessed factors influencing dietary habits. Dual-energy X-ray absorptiometry (DXA) measured lean body mass, fat mass, and body fat. A GLM multivariate analysis was used with significance accepted at p < 0.05. Significant body composition differences were observed between genders (p < 0.001) and among sports (p < 0.001). Dinner (83.7%), lunch (67.4%), and breakfast (55.4%) were the most frequently eaten meals, followed by evening snack (17.8%), afternoon snack (15.2%), and morning snack (8.7%). Greater preferences for starches were observed for HCS (p = 0.04; η2 = 0.07) and for a greater preference for vegetables was found for NCS (p = 0.02; η2 = 0.09). Significant differences also existed in the importance of health (p = 0.04; η2 = 0.07), weight control (p = 0.05; η2 = 0.11), natural content (p = 0.04; η2 = 0.07), and price (p = 0.04; η2 = 0.07). These results support our hypothesis that food choices and food preferences differ between contact types. This may help sports dieticians create more individualized nutrition programs.